2005
DOI: 10.2320/matertrans.46.697
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Electrical Properties of Laminates with Woven Carbon Fabric and Ferroelectric or Piezoelectric Particulate Epoxy due to Tensile Loading

Abstract: Measurement of electrical properties of fiber-reinforced plastics (FRPs) is an attractive method for predicting fatigue life and recording strain in FRPs. In this study, we prepared ferroelectric specimens laminated with woven carbon fabric and BaTiO 3 particulate epoxy. We measured those specimens' electrical properties during tensile testing. Electrical resistance increased slightly and the electrical capacitance decreased as the tensile stress increased up to 500 MPa. As the tensile stress increased above 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Hansen et al showed that Poly(3,4-ethylenedioxythiophene) and aliphatic polyurethane substrate retained conductive property during stretching and relaxation [16]. Kageyama et al investigated a BaTiO 3 impregnated carbon fabric, which indicated an electrical resistance during tensile tests [17]. The resistance of carbon nanotubes coated textile capacitor was studied by Yun et al which investigated the behavior of resistance during mechanical strain in textile-based capacitors consisting of Carbon nanotubes coated fabrics [18].…”
Section: Introductionmentioning
confidence: 99%
“…Hansen et al showed that Poly(3,4-ethylenedioxythiophene) and aliphatic polyurethane substrate retained conductive property during stretching and relaxation [16]. Kageyama et al investigated a BaTiO 3 impregnated carbon fabric, which indicated an electrical resistance during tensile tests [17]. The resistance of carbon nanotubes coated textile capacitor was studied by Yun et al which investigated the behavior of resistance during mechanical strain in textile-based capacitors consisting of Carbon nanotubes coated fabrics [18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the vibration A survey of the published literature shows that process modeling of CMCs has been studied by a number of researchers. Processes that have been modeled include RMI, 15,16 CVD, 17,18 CVI, [19][20][21][22] and Sol-Gel Infiltration. 23 Impregnation of alumina matrix in eight-harness satin Nextel 610 fabric has been studied numerically in Ref.…”
Section: Methodsmentioning
confidence: 99%
“…13 On the other hand, a piezoelectric ceramic is also expected to act as an energy-harvesting material. [14][15][16][17] Kageyama et al 18 investigated energy-harvesting performance during tensile and fatigue tests of lead zirconate titanate (PZT) particle-dispersed CFRP. Hwang et al 19 also dispersed PZT in FRP and investigated its output voltage.…”
mentioning
confidence: 99%
“…The piezoelectric elements, such as ZnO nanowires, have been reported to be hydrothermally grown onto the aramid fabrics as a composite energy generator [16]. Alternatively, a sandwich structure was developed by embedding the piezoelectric component between two composite laminates [16][17][18]. The direct integration of macro fibre composite (MFC) with the composite laminate for harvesting energy was also experimentally [20] and numerically [21] assessed based on the various vibration inputs at different application scenarios.…”
Section: Introductionmentioning
confidence: 99%